Perceptions of efficacy, control, and risk: a theory of mixed control - Erik Monsen; Diemo Urbig (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Based on the aggregated insights of the existing theories related to multiple sources of efficacy and locus of control, we introduce the theory of mixed control, a model of compound-risk perception. This theory considers outcome expectancies as being composed of expectancies regarding three distinct sources of risk (self, others, and chance). This reflects that entrepreneurship is a complex and dynamic activity, involving multiple sources of risk. Beliefs about the efficacy of these elements are weighted by the degree to which these elements are perceived to control the outcome. The interaction of efficacy and control beliefs is therefore at the core of our theory. Further, we discuss that risks are not only subjectively perceived but can be endogenous and depend on future decisions and actions of the entrepreneur.
Keywords: D8; D83; D84; 330; Locus of control; self-efficacy; risk perception; Risikopräferenz; Wahrnehmung; Meinung; Erwartungstheorie; Persönlichkeitspsychologie; Entscheidung bei Unsicherheit; Theorie